Identifikasi Hambatan Belajar Online Siswa pada Masa Pandemi COVID-19 (Study Kasus: di Madrasah Tsanawiyah) - Ahmad Ahmad; Habib Ratu Perwira Negara; Parihin Parihin; Sahrizal Fahlawi; Heri Fadli (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The purpose of this study was to find out the online learning Obstacles of Madrasah Tsanawiyah students during the COVID-19 pandemic in Montong Sapah Village. The method used in this research is the descriptive qualitative method, where the data obtained will be described in detail so that clear information is obtained. The data sources in this study are madrasah heads, teachers, students, and parents. From the data, the source obtained data in the form of interview results. While the results obtained from this study are that there are several obstacles for teachers and students in online learning during the COVID-19 pandemic, namely 1). Mastery of basic materials is still lacking. 2). Can not use online media properly and 3). The motivation to learn online students is still lacking. 4). Unstable internet network. 5). Availability of facilities and infrastructure in madrasahs is still lacking. 6). The media used by teachers has not been able to attract students and 7). The economic condition of teachers and students who are still in the lower middle class. an alternative to overcome the learning barriers is 1). Holding a Wi-Fi network for teachers, 2). Conducting training using online learning applications for teachers and students. 3). Provide facilities and infrastructure for teachers to conduct online learning, and 4). Microsoft Office training for teachers.